Determining the Number of Refugees to Be Resettled in the United States: An Ethical and Policy Analysis of Policy-Level Stakeholder Views. Issue 2 (3rd April 2021) - Fabi, Rachel; Serwer, Daniel; Singh, Namrita S.; Persad, Govind; Spiegel, Paul; Rubenstein, Leonard
Abstract: Through engagement with key informants and review of ethical theories applicable to refugee policy, this paper examines the ethical and policy considerations that policy-level stakeholders believe should factor into setting the refugee resettlement ceiling. We find that the ceiling traditionally has been influenced by policy goals, underlying values, and practical considerations. These factors map onto several ethical approaches to resettlement. There is significant alignment between U.S. policy interests and ethical obligations toward refugees. We argue that the refugee ceiling should be restored to historical norms, and that there exists a corresponding obligation to counter negative public perceptions about refugees and the costs of resettlement.